Analisis Pengaruh Kepuasan Gaji, Kepuasan Kerja, Komitmen Organisasional Terhadap Turnover Intention Perawat di Rumah Sakit Islam Jakarta Cempaka Putih - Haekal Nafiz, Muhammad (PT. Alahyan Publisher Sukabumi, 2024)
Turnover intention can be interpreted as the movement of labor out of the organization. The high level of turnover intention has become a serious problem for many companies, even some companies experience frustration when they find out that the recruitment process that has succeeded in attracting qualified staff ultimately turns out to be useless because the recruited staff has chosen a job in another company. The purpose of this study is to analyze the influence of salary satisfaction, job satisfaction, and organizational commitment on the turnover intention of nurses at the Jakarta Cempaka Putih Islamic Hospital. This study uses an observational analytical method with a cross-sectional design. Data collection was carried out by interviews, surveys and questionnaire distribution. The data analysis technique used is PLS (partial least square). The results of this study found that there was an effect of salary satisfaction on turnover intention, job satisfaction did not have a significant effect on turnover intention and there was no effect of organizational commitment on turnover intention. The researcher's suggestion is to further review both the number and the existing payroll system, provide a transparent assessment of nurses' performance, increase nurses' job satisfaction, and fulfill nurses' rights following the accuracy of remuneration, career leveling, and suitability in assignments.